ChemInform Abstract: Lewis Acid Catalyzed [3 + 2]‐Annulations of Donor—Acceptor Cyclopropanes and Ynamides. Issue 35 (2nd September 2014) - Mackay, William D.; Fistikci, Meryem; Carris, Ryan M.; Johnson, Jeffrey S.
Abstract N, N‐Dimethylaniline as well as 4‐chlorophenyl substituted cyclopropane analogues fail to react.